Implementation of Experiential Learning Model to Improve Science Process Skills - Jannah, Sabrina Firdatul; Shofiyah, Noly (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
Data collection in this study aims to describe the effect of the experiential learning model on improving student's science process skills. The factor that causes low science process skills is that teachers. The experiential learning model is a learning model that implements a direct student learning process. This study uses a quantitative approach with experimental methods. The type of research research is a one-group pre-test and post-test design. The sample in this study was using a saturated sampling of 22 students. The research instrument is science process skills (KPS) test questions oriented to description and multiple choice questions. Data were analyzed descriptively quantitatively by normality test for normal data testing and normalized gain-score test to see the improvement of students' KPS. In addition, it is known how much the KPS increase using the N-Gain Test is 0.51, with a moderate category included in the normalized gain criteria of 0.3 ≥ g ≤ 0.7. Based on the results of the research data obtained, the average score on the pre-test was 59.09, while the average score on the post-test showed an increase to 80. This research proves that learning using the Experiential Learning model can make students understand the material in depth, which is taught through the search process carried out by students.